(untitled) (Acta Entomologica Serbica, 2019)
We examined 638 Lepidoptera specimens on the territories of 13 European countries in our search for parasitoids. We collected eggs, larvae and pupae. In total, 251 Lepidoptera species were identified, belonging to 169 genera from 30 families. Of the total sample, approximately one-third (32.23%) were parasitized. In 168 samples (26.42%), we identified only one parasitoid species per host. In addition to these data, 224 plant species from 114 genera were identified, of which the vast majority were feeding plants.